What happens when savings groups grow up? Examining savings group sustainability and perceived long-term benefits. Issue 4 (19th May 2021) - Moret, Whitney; Swann, Mandy; Lorenzetti, Lara
ABSTRACT: Using qualitative methods, this article examines savings groups that have been in operation for five to ten years in Tanzania to understand internal and external factors influencing savings group longevity and explore member perception of how long-term participation affected the well-being of their households and children. Although groups did not consistently adhere to best practices, they viewed good leadership, trust, and love as the most important factors for sustainability. Poor loan repayment, low savings rates, and dependence on external support represented the greatest challenges to sustainability. Respondents perceived ongoing positive outcomes across several areas of well-being for their households and children.